2014
DOI: 10.1108/cms-08-2011-0065
|View full text |Cite
|
Sign up to set email alerts
|

Occupational commitment, industrial relations and turnover intention

Abstract: Purpose – The aim of this research is to study the relationships between occupational commitment, industrial relations and turnover intention, as well as the moderating role of turnover intention. Design/methodology/approach – Empirical data for this study were collected using a questionnaire survey method. A total of 600 copies of the questionnaire were sent out by post or email to firms and 429 valid responses were finally obtained, yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 73 publications
(105 reference statements)
0
17
0
Order By: Relevance
“…Whereas Somer (1995) found a negative association between the same in US healthcare sector, thus, culture and sector may have an effect. In addition, Yuan et al (2014) suggested employers focusing on their employees’ occupational commitment to reduce turnover intention. The study also noted that alternative job opportunities moderate the negative association of job satisfaction and professional commitment with leave intention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas Somer (1995) found a negative association between the same in US healthcare sector, thus, culture and sector may have an effect. In addition, Yuan et al (2014) suggested employers focusing on their employees’ occupational commitment to reduce turnover intention. The study also noted that alternative job opportunities moderate the negative association of job satisfaction and professional commitment with leave intention.…”
Section: Discussionmentioning
confidence: 99%
“…A four-item scale from the studies of Weng and McElroy (2012) and Yuan et al (2014) was used to measure alternate job opportunity. Huang et al (2017) used the same scale and reported 0.84 as its internal consistency.…”
Section: Methodsmentioning
confidence: 99%
“…Employee turnover in emerging economies, such as China, has drawn increasing attention in labor literature (Liu et al, 2013;Xiao and Cooke, 2012;Yuan et al, 2014). In the past, most organizations in China relied on government allocations of labor to meet their development requirement.…”
Section: Introductionmentioning
confidence: 99%
“…We also eliminated other possible effects of individuals’ demographic features on job performance by using several control variables. Employees’ gender and age are two factors suggested by previous studies as influential factors on performance and attitude (Ng and Feldman, 2010), and as Yuan et al (2014) suggest that employees with a higher education level may have higher job performance, we controlled the education level of team members. Moreover, we also added team size as a control variable to offset its possible effect on LMX (Erdogan and Bauer, 2010).…”
Section: Methodsmentioning
confidence: 99%